Analisis Perilaku Prokrastinasi Akademik pada Mahasiswa - Wahyudi Jisaid; Nurdin; Rahmawati; Sitti Fauziah; Muh. Ikhsan (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss procrastination behavior in students. This study uses a qualitative approach with a descriptive method of literature study. The results of this study indicate that student procrastination behavior can have positive and negative impacts. This study concludes that delays made can have a positive impact if it is accompanied by additional insight or references related to the given task. However, procrastination that often occurs in students usually has a negative impact because the procrastination process is often filled with something less productive.